Pengaruh pemanfaatan batang pisang (Musa paradisiaca) dengan komposisi yang berbeda untuk menumbuhkan Maggot (Hermetia illucens) - Frid Agustinus; Infa Minggawati (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2019)
This study aims to determine the effect utilization of banana stem with a mixture of tofu waste and bran with different compositions on the average weight and number of maggot populations. The study used different media compositions: Treatment A consists of 5 kg of dried banana stems, 3 kg of tofu waste, and 2 kg of bran. Treatment B consists of 5 kg of dried banana stems, 4 kg of tofu waste, and 3 kg of bran. Treatment C consists of 5 kg of dried banana stems, 5 kg of tofu waste, and 4 kg of bran. The results of this study indicate that the use of banana stems mixed with tofu and bran can be a medium for maggot growth. Treatment C showed better results, with the average weight of 173.8 grams and total population of 6.111 maggot than treatment A and treatment B. The statistical test results at the confidence interval of 95 % indicate that different compositions have significantly different effects on the average maggot weight and total maggot population. Keywords : composition, banana stem, maggot.